A butterfly shaped Eu4(OH)2 cluster-based luminescent metal–organic framework with Lewis basic triazole sites demonstrating turn off sensing in the presence of organic amines. Issue 1 (6th December 2022) - Wang, Jie-Ru; Fu, Jin; Zhang, Yu-Juan; Liang, Jia-Chen; Zhou, Rui-Sha; Gong, Si-Min; Song, Jiang-Feng
Abstract : According to hard and soft acid base theory, a novel 3D butterfly shaped Eu4 (OH)2 cluster-based metal organic framework with lewis basic triazole sites is successfully obtained and shows sensitive luminescence quenching responses to organic amines. Abstract : The effective detection of organic amines is particularly important for environmental protection and human health. Herein, according to hard and soft acid base theory, a novel three-dimensional (3D) butterfly shaped Eu4 (OH)2 cluster-based metal–organic framework with Lewis basic triazole sites, [Eu4 (taip)4 (ox)(OH)2 (H2 O)4 ]·3H2 O n (1 ) (H2 taip = 5-(1, 2, 4-triazol-1-yl) isophthalic acid, H2 ox = oxalic acid), was successfully synthesized under solvothermal conditions, and was characterized by single crystal X-ray diffraction, powder X-ray diffraction, elemental analysis, infrared spectroscopy and thermogravimetric analysis. Structural analysis reveals that compound 1 is a 3D net constructed from butterfly shaped Eu4 (OH)2 clusters and contains isosceles triangular channels with dimensions of 8.84 × 8.84 × 8.63 Å 3, which shows an unprecedented 8-connected topology with a Schläfli symbol 3 6 ·4 18 ·5 3 ·6. Fluorescence experiments of compound 1 show sensitive luminescence quenching responses to organic amines such as diethylamine (DEA), trimethylamine (TMA), triethylamine (TEA), ethylenediamine (EDA) and aniline, and the quenching constants ( K SV ) decrease in the following order: EDA > DEA > TMA > TEA > aniline. The fluorescence quenching responses may be attributed to the energy gap between the LUMO energy values of H2 taip and organic amines, which hinders the transfer of excited state energy to the emission state of Eu 3+ and results in luminescence quenching. The fluorescence lifetimes of compound 1 in ethanol and organic anilines indicate that the fluorescence recognition process of organic amines was static.